Treatment of adult ALL patients with third-generation CD19-directed CAR T cells: results of a pivotal trial - Maria-Luisa Schubert; Anita Schmitt; Angela Hückelhoven-Krauss; Brigitte Neuber; Alexander Kunz; Philip Waldhoff; Dominik Vonficht; Schayan Yousefian; Lea Jopp-Saile; Lei Wang; Felix Korell; Anna Keib; et al. (Journal of Hematology & Oncology, 2023)
Abstract Background Third-generation chimeric antigen receptor (CAR)-engineered T cells (CARTs) might improve clinical outcome of patients with B cell malignancies. This is the first report on a third-generation CART dose-escalating, phase-1/2 investigator-initiated trial treating adult patients with refractory and/or relapsed (r/r) acute lymphoblastic leukemia (ALL). Methods Thirteen patients were treated with escalating doses of CD19-directed CARTs between 1 × 106 and 50 × 106 CARTs/m2. Leukapheresis, manufacturing and administration of CARTs were performed in-house. Results For all patients, CART manufacturing was feasible. None of the patients developed any grade of Immune effector cell-associated neurotoxicity syndrome (ICANS) or a higher-grade (≥ grade III) catokine release syndrome (CRS). CART expansion and long-term CART persistence were evident in the peripheral blood (PB) of evaluable patients. At end of study on day 90 after CARTs, ten patients were evaluable for response: Eight patients (80%) achieved a complete remission (CR), including five patients (50%) with minimal residual disease (MRD)-negative CR. Response and outcome were associated with the administered CART dose. At 1-year follow-up, median overall survival was not reached and progression-free survival (PFS) was 38%. Median PFS was reached on day 120. Lack of CD39-expression on memory-like T cells was more frequent in CART products of responders when compared to CART products of non-responders. After CART administration, higher CD8 + and γδ-T cell frequencies, a physiological pattern of immune cells and lower monocyte counts in the PB were associated with response. Conclusion In conclusion, third-generation CARTs were associated with promising clinical efficacy and remarkably low procedure-specific toxicity, thereby opening new therapeutic perspectives for patients with r/r ALL. Trial registration This trial was registered at www.clinicaltrials.gov as NCT03676504.